Analisa Kepuasan Mahasiswa Terhadap Kegiatan Belajar Mengajar Di Program Studi Teknik Informatika Universitas Mataram Menggunakan Metode Importance Performance Analysis - Diaz Guntur Febrian; Nadiyasari Agitha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2020)
This study discusses "Student Satisfaction Analysis on Teaching and Learning Activities in Informatics Engineering Program University of Mataram Using Importance Performance Analysis Method". Students are required to fill out a teaching and learning questionnaire from all courses. The questionnaire consisted of questions relating to teaching and learning activities. Students give perceptual value and expectation value on every questionnaire question. Then the relationship between perceptual value and expectation value is analyzed using Importance Performance Analysis method. From the analysis results can be known which variables should be prioritized for improvement and which variables are excessive and does not require priority.